A dual‐band shared‐aperture parasitic array radiator antenna for WLAN applications. Issue 11 (20th July 2021) - Liang, Qiuyan; Sun, Baohua; Zhou, Gaonan
Abstract: In this article, a dual‐band shared‐aperture parasitic array radiator (DS‐PAR) antenna is presented to cover 2.4‐GHz WLAN lower‐band (LB) and 5‐GHz wireless local area network (WLAN) higher‐band (HB). The proposed antenna uses parasitic elements shared by both frequency bands, thus achieving the shared aperture of the dual‐band array. The antenna comprises of active elements for two bands, shared parasitic elements, reflective plate, and ground plane. The shared parasitic elements have different functions in the two frequency bands. The reflection parasitic elements in HB can be used in LB to achieve impedance matching and optimize the half‐power beamwidth. With a rotational symmetric structure, the antenna can generate three beams in 2.4‐GHz LB and six beams in 5‐GHz HB in horizontal plane, which covers full 360° range in both bands without communication blind zone. To validate the proposed design, a prototype is fabricated and measured. With the shared reflective plates, the dual‐band antenna works well in a shared space with a diameter of 0.73 wavelength in free space at 2.45 GHz. The antenna exhibits good impedance matching and high‐port isolation higher than 20 dB over the 2.4‐ and 5‐GHz bands. The realized gain is 4.81, 5.37, 5.30 dBi at 2.45, 5.25, and 5.8 GHz, respectively. The envelope correlation is lower than −35 dB within the bands of interest.